Evaluation and degradation after soil burial and fungal attack on particleboard made using Glutardialdehyde modified corn starch as a binder - M.H. Amini; R. Hashim; N.S. Sulaiman; M. Mohamed; M.S.M Rasat; M.N. Masri; B.J. Geng (2016)
This work evaluates the particleboard made using glutardialdehyde modified corn starch as a binder in contact with soil and after exposed to fungal attack. Glutardialdehyde modified corn starch was used as a more environmentally friendly binder compared to conventional, formaldehyde based binder. Binder mixed with rubberwood particles, poured into 20 cm x 20cm x 0.5 cm mould and pre-pressed to form mat. Mat was hot-pressed at 150C for 15 minutes for the binder to cure. Three densities of particularboards were made which were 0.6 g/cm3, 0.7 g/cm3 and 0.8 g/cm3. Soil burial test was done for 4 weeks and 8 weeks in controlled condition. Fungal exposure test were done using Schizophyllum commune, Pycnoporus sanguineus, Formitopsis palustris and Trametes versicolor species. Both tests were done following British Standard (DD ENV 807:2001). It was found out that using glutardialdehyde modified starch as particleboard binder had increased the resistivity of the wood based composite against soil degrading agents and fungal attack, compared to those made using native starch as the binder. This is due to better crosslinking of the aldehyde groups which made the particleboard stronger and harder for the degrading agents to penetrate. However, particleboard with different density levels did not affect their percentage of degradation as no trend of increment or decrement were seen with increasing density level.